(untitled) (Journal of Social Sciences Review, 2023)
Climate change is causing more global warming today, which has an impact on every sector of the economy. In order to avoid financial damage as a result of climate change, it is necessary to validate the policies for policymakers and government authorities. The aim of this study is to measure the impact of climate change on food security in selected developing economies. The results indicate that climatic variations have a positive long-run impact on food security in selected developing countries due to extended growing seasons and fertilization effects. On the other hand, energy consumption and rapid urbanization are deteriorating the food security situation significantly over time due to the costlier energy and unplanned urban sprawl in most of the region. The study suggests that we need to learn from developed nations by using sustainable urbanization planning and liberalizing energy prices for agricultural consumption to fight hunger and food insecurity in these economies.